1038 Patient's Experiences and Lessons Learned Following Establishment of a New Regional Day Procedure Centre in Response To COVID-19 Pandemic. (12th October 2021) - Gilmore, C; Coulson, R; Graham, V; McAllister, I
Abstract: Aim: Due to the impact of COVID-19 on elective services an exclusive day procedure centre has been established for the region. This study aims to review the patient experiences of the service. Method: A 26-question feedback survey assessed patient outcomes, complications, and experiences. All patients who underwent hernia repair from September to November 2020 were contacted 6 weeks postoperatively by telephone to participate. Results: Over 10 weeks, 55 patients underwent unilateral inguinal hernia repair. 49 patients completed the survey, 5 patients were not contactable, and 1 patient declined to participate. Overall high levels of patient satisfaction were reported, when asked the question "Rate the overall experience (out of 10) from the time you were contacted to proceed with surgery to now?" The average patient reported score was 9.5. Results indicated excellent use of written patient information leaflets. 92% (N = 46) of participants had a travel time of less than 60 minutes and 94% (N = 45) of those contacted reported the centre as a convenient location. Qualitative responses described pain at 48-72hrs following the procedure when local anaesthetic had worn off, to the detriment of overall patient satisfaction. Conclusions: A dedicated site for day-surgery can be successful during the period of COVID-19 restrictions. High levels of patient satisfaction reported. However, lessons learned include need for improved education regarding postoperative analgesia; the effects of local anesthesia and patient directed follow up via the well-established local surgical hub.